Light modulation of ferredoxin mRNA abundance requires an open reading frame. - Dickey, L F (1994)
Ferredoxin I (Fed-1) mRNA abundance is modulated by an internal light regulatory element that includes sequences both 5' and 3' of the translational initiation site. To test the hypothesis that the light response mediated by this element might be coupled to translation, we transformed tobacco plants with gene constructs blocked in translational initiation or elongation. Here, we report that such mutations abolish the light response in vivo. A nonsense mutation could be rescued by restoring the open reading frame with a different sequence, even when the new codon caused an amino acid substitution. Our data establish that the light response requires a translatable reading frame and thus provide strong circumstantial evidence for post-transcriptional modulation of Fed-1 mRNA levels. The Fed-1 system is presently the only higher plant example of a developmentally regulated change in mRNA abundance that requires translation of the affected mRNA.